Assessment of Sodium and Potassium Intakes in Children Aged 6 to 18 Years by 24 h Urinary Excretion in City of Rabat, Morocco - Naima Saeid; Mohammed Elmzibri; Abdeslam Hamrani; Qandoussi Latifa; Hakim Belghiti; Hicham El Berri; Kaoutar Benjeddou; Amina Bouziani; Hasnae Benkirane; Youness Taboz; Asmae Elhamdouchi; Khalid El Kari; et al. (Journal of Nutrition and Metabolism)
Background. The incidence of noncommunicable diseases (NCDs) has greatly increased, mainly due to high level of dietary sodium. Thus, reduction of sodium intake in population has been recognized as one of the most cost-effective strategies to reduce NCDs. The aim of this study was to estimate sodium and potassium consumption in a sample of Moroccan children as a baseline study to implement national strategy for salt intake reduction. Methods. The study was conducted on 131 children aged 6–18 years recruited from Rabat and its region. Sodium excretion and potassium excretion were measured on 24 h urinary collection, and the creatinine excretion was used to validate completeness of urine collections. Results. The average of urinary sodium was 2235.3 ± 823.2 mg/day, and 50% of children consume more than 2 g/d of sodium (equivalent to 5 g/day of salt), recommended by the WHO. However, daily urinary excretion of potassium was 1431 ± 636.5 mg/day, and 75% of children consume less than adequate intake. Sodium consumption increased significantly with age. Of particular interest, 46.7% of children aged 6–8 years and 49.3% of children aged 9–13 years consume more than the corresponding upper limits. Conclusions. Children have high sodium and low potassium status. There is evidence of the urgent need to implement a strategy for reduction of dietary sodium intake in Morocco.